Cultural Values, Norms And Lifestyle In Shaping Consumer Loyalty: The Moderating Role Of Digital Engagement - Ansari Jayanti; Mulawarman Munsyir; Hasnidar; Tasrim (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
This study examines the influence of cultural values, social norms, and lifestyle on consumer loyalty toward Roti Maros, a prominent local brand in South Sulawesi, Indonesia, while assessing the moderating role of digital engagement. The research is motivated by the increasing integration of cultural identity and digital behavior in shaping consumer-brand relationships, particularly in local product contexts that face the challenge of maintaining authenticity amid digital transformation. Employing a quantitative approach with a structured survey method, data were collected from 191 respondents who are repeat consumers of Roti Maros. The data were analyzed using Structural Equation Modeling (SEM) with WarpPLS to test direct and moderating relationships among latent constructs. However, digital engagement does not significantly moderate the relationship between cultural values and loyalty, and even shows an adverse moderating effect between norms, lifestyle, and loyalty. These findings suggest that while digital platforms enhance brand interaction, excessive digital reliance may weaken the cultural and social bonds that traditionally foster loyalty. The study contributes to understanding consumer behavior by integrating cultural and digital perspectives, offering managerial insights for developing culturally grounded yet digitally balanced marketing strategies.